Finance and growth: New evidence from Meta-analysis - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
Purpose In a meta-study, we have bridged the gap between the pros and cons of a questionable finance-growth nexus. Design/methodology/approach Over 20 fundamental characteristics that have influenced the debate over the last decades have been examined. The empirical evidence is based on 196 outcomes from 20 studies. We assess the degree of heterogeneity and identify causes of the observed differentiation. Findings Our findings also show evidence of publication bias. Overall, a genuine effect exists between financial development and economic growth. A finance-growth nexus might not be appealing in our era because of: endogeneity-based estimations, publication bias and, effects of financial activity. A historical justification has also been discussed. Practical implications Encouraging the publication of results with findings that are not consistent with the mainstream positive finance-growth nexus should provide new scholarly insights into the relationship. Depending on the specific context of sampled countries, the role of policy has also been to encourage financial development through measures that may expose countries to negative external shocks like financial crises. Policy makers that have been viewing the challenges of development exclusively from this point of view for the rewards of growth may not be getting the financial dynamics correctly. Originality/value Very few meta-analysis studies have focused on the finance-growth nexus.
Keywords: C1; C4; E0; O0; 330; Meta analysis; Finance; Economic growth; Publication bias